A menina que roubava livros: uma abordagem dialógica de leitura em sala de aula - Silva, Bruno Athaliba dos Anjos (2019)
The Bakhtin Circle comprehends every discursive communication as a dialogical relation. In this bias, the meaning will only be formed through an interaction (independently of being written or oral), in which the subjects answer to the statements that are presented from a responsive active comprehension (from which are effective through means of concordance, discordance, complementation or application). However, historically, there is, in brazilian schools - above all of public network -, a setback in this relation, as far as the procedure impedes the dialogical ethos and the pleasure of reading, necessary elements for the formation of critical reader. In sight of that, with the goal of discussing the formation of the reader in an elementary school classroom, we present, in this work, an experiment with the romance “The Book Thief”, in the 7º year of elementary school of a public school of Natal. For the systemization of this work, there was a focus upon three pillars, reading pleasure, criticism and the conceptions of language (whilst dialogical construction). The theoretical fundamentation is founded upon the conceptions of the Bakhtin Circle, in what concerns the comprehension of language as social construct and historically situated and the discursive genres as historical constructs and instruments of interaction in the different spheres of human activity. The methodology is fundamented on a dialogical perception, having as methodological procedure the creation of workshops with the objective of promoting the reading of the book. The research is anchored in a qualitative-interpretivist approach and the data built on the scope of Professional Master’s degree in Literature-ProfLetras. The results point that the work in Portuguese Language classrooms can be amplified with a dialogical conception of language and reading. It is presented as product of this work a pedagogical notebook that systematizes every accomplished activities and guides future actions in different contexts.